Proceedings of the Third Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2019
DOI: 10.2991/piceeba-19.2019.86
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Capital, Motivation and Job Satisfaction on Employee Performance: A Literature Review

Abstract: This paper is a literature study to analyze the effect of human capital, motivation and job satisfaction on employee performance. This type of research is explanatory research, looking at the relationship among free variables human capital, motivation, and job satisfaction on employee performance. The purpose of this study is to collect and analyze the published articles regarding the effect of human capital, motivation, and job satisfaction on employee performance. The research design is a literature review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It showed by the value of Chi-Square 59.303 in the training independent variable, the score of chi-square70.862 in the education variable, and 130.862 in the variable of experience (Philip & Ikechukwu, 2018). Besides, another study that is not in line with the researcher is (Jeki & Sulastri, 2019), who studied several literatures related to the influence of human capital towards employee performance showing positive and significant result. Another notion from (Rakhmalina et al, 2017), also disclose the different and convenient management of human resources will generate good output for the company.…”
Section: Resultsmentioning
confidence: 97%
“…It showed by the value of Chi-Square 59.303 in the training independent variable, the score of chi-square70.862 in the education variable, and 130.862 in the variable of experience (Philip & Ikechukwu, 2018). Besides, another study that is not in line with the researcher is (Jeki & Sulastri, 2019), who studied several literatures related to the influence of human capital towards employee performance showing positive and significant result. Another notion from (Rakhmalina et al, 2017), also disclose the different and convenient management of human resources will generate good output for the company.…”
Section: Resultsmentioning
confidence: 97%
“…His study found that HCD and JS have a substantial connection. Evidence also emerged recently from the study of Jeki and Sulastri (2019) that HCD has a positive linear relationship with JS. This means the employees are better off learning new things and more satisfied with their jobs when they successfully apply innovative ideas.…”
Section: Review Of the Related Literaturementioning
confidence: 96%
“…One way to do this is by developing mentoring programs that pair experienced HCD practitioners with eager trainees. In addition, offering employees the chance to demonstrate their HCD abilities and contributions may enhance their motivation and sense of achievement (Jeki, 2019). Moreover, it was shown that personalized development plans that not only correspond to the objectives of the organization but also to the individual's career ambitions and interests were very successful in enhancing motivation and performance.…”
Section: Soft Skills Developmentmentioning
confidence: 99%